Health Belief Model on the Choice of Medical Doctor among Mothers of Children with Diarrhea - Prita Yuliana Irnawati; Harsono Salimo; Yulia Lanti Retno Dewi (Journal of Health Promotion and Behavior, 2018)
Background: